PENGARUH HARGA SAHAM, VOLUME PERDAGANGAN DAN VARIAN RETURN TERHADAP BID-ASK SPREAD PADA MASA SEBELUM DAN SESUDAH STOCK SPLIT - Kanaya Lapae (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this research is to see how the influence of stock price, trading volume, and return variance affect the Bid-ask spread, both before and after the stock split. The population of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019 is used in this analysis. The sampling technique used purposive sampling, which resulted in a sample of 26 companies. This research relies on secondary data, particularly the company's financial statements, which can be viewed on the official website of the Indonesia Stock Exchange (IDX). Multiple linear regression was used as the analytical method. The results showed that before the stock split, stock prices had a negative effect on the Bid Ask Spread, while trading volume and Variant Return had no effect on the Bid Ask Spread. After the stock split, the stock price and trading volume on the bid ask spread have no effect.